Applications of covalent chemistry in targeted protein degradation. (26th October 2022) - Lu, Dong; Yu, Xin; Lin, Hanfeng; Cheng, Ran; Monroy, Erika Y.; Qi, Xiaoli; Wang, Meng C.; Wang, Jin
Abstract : This review summarizes the recent work of covalent chemistry in targeted protein degradation and describes the concept, pros and cons, development, and the outlook of covalent PROTACs. Abstract : Proteolysis-targeting chimeras (PROTACs) and targeted covalent inhibitors (TCIs) are currently two exciting strategies in the fields of chemical biology and drug discovery. Extensive research in these two fields has been conducted, and significant progress in these fields has resulted in many clinical candidates, some of which have been approved by FDA. Recently, a novel concept termed covalent PROTACs that combine these two strategies has emerged and gained an increasing interest in the past several years. Herein, we briefly review and highlight the mechanism and advantages of TCIs and PROTACs, respectively, and the recent development of covalent PROTACs using irreversible and reversible covalent chemistry.